Tephra identification and radiocarbon chronology of sediment from Paitan Lake at the northern part of Luzon Central Plain, Philippines. (15th October 2017) - Nakanishi, Toshimichi; Torii, Masayuki; Yamasaki, Keiji; Bariso, Ericson; Rivera, Danikko John; Lim, Robjunelieaaa; Pogay, Cathy; Daag, Arturo; Hong, Wan; Nakamura, Toshio; Fujiki, Toshiyuki; Okuno, Mitsuru
Abstract: In order to construct the tephrostratigraphy of the northern region of the Philippines, two sediment cores were obtained from Paitan Lake. Paitan Lake is located in the northern part of Luzon Central Plain, 88 km northeast of Pinatubo Volcano. It's a crater lake with a surface area of 0.8 km 2 . Its drainage basin has an area of 38.5 km 2 and has an outflow-river with a width of only a few meters. These cores consisted of two units: (1) an upper alternating bed of mud and peaty layers, from depths 0–6 m; and (2) a lower dark gray to gray mud bed, obtained from depths 6–28 m. Eight tephras were recognized, on the split surface of the cores. Radiocarbon ages of seven plant fragments, from 1.50 to 13.41 m depths, and twelve organic sediments, from 4.72 to 28.00 m depths were measured by the AMS facilities of KIGAM, Nagoya University and Institute of Accelerator Analysis Ltd. These results were 1.6–24 cal kBP. These ages of tephras were correlated to the eruption periods of Pinatubo and Natib Volcano.